2022
DOI: 10.3389/fpsyt.2022.923025
|View full text |Cite
|
Sign up to set email alerts
|

Usual care for youth with autism spectrum disorder: Community-based providers’ reported familiarity with treatment practices

Abstract: ObjectiveTo examine patterns and predictors of familiarity with transdisciplinary psychosocial (e.g., non-pharmacologic) practices for practitioners treating youths with autism spectrum disorder (ASD) in the United States.MethodPractitioners (n = 701) from behavioral, education, medical, and mental health backgrounds who worked with youth (ages 7–22) with ASD completed the Usual Care for Autism Survey, which assessed provider demographics and self-reported familiarity with transdisciplinary treatment practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Of the 55 practices that comprised the full UCAS survey inventory, we focused on a subset of 32 practices that were endorsed, based on expert consensus ( 38 ), as treatments for all three of the identified key treatment areas: social challenges, externalizing symptoms, and anxiety. As in Lerner et al ( 40 ), we did not include the remaining 23 practices in the analysis for this paper since they were identified by experts as specific (e.g., endorsed by experts in treating anxiety only), rather than transdiagnostic (endorsed for treating all 3 presenting problems). We included only these 32 transdiagnostic strategies because the purpose of the present study was to focus on coherent sets of intervention practices that are used by providers to treat autistic youth regardless of the treatment area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 55 practices that comprised the full UCAS survey inventory, we focused on a subset of 32 practices that were endorsed, based on expert consensus ( 38 ), as treatments for all three of the identified key treatment areas: social challenges, externalizing symptoms, and anxiety. As in Lerner et al ( 40 ), we did not include the remaining 23 practices in the analysis for this paper since they were identified by experts as specific (e.g., endorsed by experts in treating anxiety only), rather than transdiagnostic (endorsed for treating all 3 presenting problems). We included only these 32 transdiagnostic strategies because the purpose of the present study was to focus on coherent sets of intervention practices that are used by providers to treat autistic youth regardless of the treatment area.…”
Section: Methodsmentioning
confidence: 99%
“…We included only these 32 transdiagnostic strategies because the purpose of the present study was to focus on coherent sets of intervention practices that are used by providers to treat autistic youth regardless of the treatment area. As Lerner et al ( 40 ) noted in a previous study involving transdiagnostic practices on the UCAS, “If a practice was identified to be specific only to the treatment of anxiety, for instance, this would likely skew its relation to other identified practices.” Thus, including only these 32 transdiagnostic practices allowed us to identify the practices sets likely to be most generalized to all types of providers who serve autistic youth ( 40 ). First, participants rated their familiarity with each practice on a 4-point Likert scale (1 = never heard of/not at all familiar ; 4 = very familiar ) ( 40 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations